The Statue of Lenin (with the Moscow Mausoleum as the background). The contribution to the biography - Pogonowska, Ewa (Porównania, 2022)
The article deals with contemporary discourse of polish reporters-travellers regarding the fate of the statues of Lenin (as well as the Mausoleum at the Red Square) after the dissolution of the Soviet Union. The issues have been presented in a wider interpretative context. The author’s particular area of interest was the “biographic” depiction of the statue, including the late (often final) stages of its “life”. Travellers who “read” and “translate” the artefacts of the Bolshevik leader’s revolution into post-Soviet words attempt to outline the socio-political background conditioning the fate of communist monuments.